2001
DOI: 10.1074/jbc.r100015200
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Pore Complex as a Transport Machine

Abstract: Nucleocytoplasmic Transport and the NuclearPore Complex Unlike their prokaryotic counterparts, eukaryotic cells separate the nuclear synthesis of DNA and RNA from cytoplasmic protein synthesis with a barrier termed the nuclear envelope (NE).1 The NE is perforated by large proteinaceous assemblies, called nuclear pore complexes (NPCs), which act as the sole gatekeepers controlling the exchange of material between the two locales (reviewed in Ref. 1). NPCs are freely permeable to small molecules (such as water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
191
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(194 citation statements)
references
References 51 publications
2
191
0
1
Order By: Relevance
“…We found that the geometrically averaged noise works well for our purposes, i.e. : (2) where I o and I b are the average measured intensities in the presence and absence of the fluorescent object, respectively, and σ o is the standard deviation of I o . This definition does not require σ o to be well-defined (if ill-or un-defined, σ o can be approximated with σ b ), and the limiting noise level at low signal is σ b , as expected.…”
Section: Localization Precisionmentioning
confidence: 87%
See 2 more Smart Citations
“…We found that the geometrically averaged noise works well for our purposes, i.e. : (2) where I o and I b are the average measured intensities in the presence and absence of the fluorescent object, respectively, and σ o is the standard deviation of I o . This definition does not require σ o to be well-defined (if ill-or un-defined, σ o can be approximated with σ b ), and the limiting noise level at low signal is σ b , as expected.…”
Section: Localization Precisionmentioning
confidence: 87%
“…First, high localization precision is necessary. NPCs are large (∼60-120 MDa), octagonally rotationally symmetric structures comprised of at least 30 different nuclear pore proteins (Nups) [1][2][3]. The pore itself is ∼90 nm in length and is ∼50 nm wide at its narrowest point.…”
Section: Visualizing Single Cargo Molecules Interacting With Nuclear mentioning
confidence: 99%
See 1 more Smart Citation
“…The transport of macromolecules across the nuclear envelope is mediated by the nuclear pore complex (NPC), an assembly of multiple copies of over 30 proteins termed nucleoporins [42,43]. Translocation across the nuclear envelope entails three steps: anchorage to the NPC, migration through the NPC and release into either cyto-or nucleoplasm [44][45][46].…”
Section: Nuclear Import and Export Mechanisms Of Smadsmentioning
confidence: 99%
“…A large subset of nucleoporins contains long phenylalanine-glycine dipeptide-containing domains (FG repeats), which are thought to form a hydrophobic/kinetic meshwork creating a barrier to most macromolecules while allowing passage of transport receptor complexes (2,8). These complexes are thought to pass the NPC by interacting with FG repeats, thus permeating the NPC core (8 -11).…”
mentioning
confidence: 99%